Prenatal and Early Childhood Exposure to Lead and Repeated Measures of Metabolic Syndrome Risk Indicators From Childhood to Preadolescence - Muciño-Sandoval, Karla; Ariza, Ana Carolina; Ortiz-Panozo, Eduardo; Pizano-Zárate, María Luisa; Mercado-García, Adriana; Wright, Robert; Maria Téllez-Rojo, Martha; Sanders, Alison P.; Tamayo-Ortiz, Marcela (Frontiers in Pediatrics, 2021)
Background: Exposure to lead (Pb) during early-life stages has been associated with the development of metabolic syndrome (MetS). Longitudinal studies of Pb exposure in critical developmental windows in children are limited. Methods: Our study included 601 mother-child dyads from the PROGRESS birth cohort. Blood lead levels (BLL) were assessed during the second and third gestational trimesters, in cord blood at delivery, and at ages 1, 2 and 4 years old. Bone lead levels in patella and tibia were assessed at 1 month postpartum and evaluated in separate models. To account for cumulative exposure (prenatal, postnatal, and cumulative) we dichotomized BLLs at each stage visit and determined: “higher” if a BLL was at least once above the median (HPb), and “lower” if all BLLs were below the median (LPb). We analyzed fasting glucose, HbA1c, triglycerides (TG), total cholesterol (TC), cHDL cholesterol, cLDL cholesterol, body mass index, waist circumference, body fat percentage, systolic (SBP) and diastolic blood pressure (DBP) at 2 study visits between 6-12 years of age and created cut-off points based on clinical guidelines for each indicator. Mixed-effects models were used to analyze each outcome longitudinally for each BLLs score, adjusting for child’s sex, size for gestational age, age, and maternal parity, age, and socioeconomic status. Results: We observed associations for HPb exposure and TC in all stages (OR=0.53, 95% CI: 0.32,0.86) and postnatally (OR=0.59,95%CI:0.36, 0.94); prenatal HPb and TG (OR=0.65, 95% CI: 0.44,0.95). HPb at all stages was associated with: WC (OR=0.27, 95% CI: 0.08, 0.86), BMI (OR=0.33, 95% CI: 0.11,0.99), SBP (OR=0.53, 95% CI: 0.32,0.85) and DBP (OR=0.57, 95% CI: 0.34,0.95). Patella bone Pb levels were associated with cHDL(OR=1.03, 95% CI: 1.00,1.07); and tibia bone Pb with TGA (OR=0.95, 95% CI: 0.91,0.99). Conclusion: Early life exposure to Pb may alter early indicators of MetS. Follow-up of these children will allow for more definition on the longer-term exposure impact.